Mechanisms of species range shift: germination and early survival of Great Basin bristlecone pine and limber pine - Smithers, Brian V.; North, Malcolm P. (Plant and soil, 2020)
Aims To examine the potential mechanistic predictors of germination and first-year survival in two species of Great Basin sub-alpine trees along an elevation gradient on three soil types. Methods Using a network of experimental gardens, we sowed limber pine and Great Basin bristlecone pine along elevational gradients at three sites on three different soil types. We collected germination and first-year survival data of each species while measuring temperature, soil water content, and other environmental variables to examine the potential predictors of first-year survival in these two species. Results Thanks to consecutive anomalously wet and dry years, we found germination and first-year survival to be largely limited by soil type, soil water content, and precipitation timing. Limber pine germination and survival showed weak negative responses while bristlecone pine germination and survival showed stronger negative responses to temperature. Conclusions Young trees are more sensitive to water limitation than to temperature and soil type has a strong moderating effect on water availability. Precipitation timing affected this availability with winter snowpack being less important in establishment than summer monsoonal rain. These results point to the importance of substrate and understanding limitations on all life stages when attempting to predict species range shifts.